Neuropsycholinguistic Analysis of the Concepts "Kindness and Love" - Bobokalonov Ramazon Rajabovich; Yo’ldosheva Sarvinoz Mahmud qizi (Scientific Trends, 2025)
This article presents a scientific discussion of the controversial conceptual features, neurological, psychological, and linguistic factors of the concepts of kindness and love. Theoretical ideas on this topic are presented within the framework of the requirements of the modern field of neuropsycholinguistics. In this article, the author addresses a pressing issue: translating neuropsycholinguistics from denominator to image — applying theory to practice across a broad range, scientifically explaining the influence of anger kindness and love on the human psyche, health, and physical activity.
Keywords: Kindness and love, hate, brain, amygdala, hypothalamus, oxytocin, vasopressin, dopamine, adrenaline, noradrenaline, neuromodulator, prefrontal cortex, insula, anger, amygdala, limbic system, cingulate gyrus, cortisol.